Mortality in COVID-19 patients with acute respiratory distress syndrome and corticosteroids use: a systematic review and meta-analysis. (1st November 2020) - Hasan, Syed Shahzad; Capstick, Toby; Ahmed, Raees; Kow, Chia Siang; Mazhar, Faizan; Merchant, Hamid a; Zaidi, Syed Tabish Razi
ABSTRACT: Objectives: The acute respiratory distress syndrome (ARDS) secondary to viral pneumonitis is one of the main causes of high mortality in patients with COVID-19 (novel coronavirus disease 2019). We systematically reviewed mortality in COVID-19 patients with ARDS and the potential role of systemic corticosteroids in COVID-19 patients. Methods: Electronic databases and country-specific healthcare databases were searched to identify relevant studies/reports. The quality assessment of individual studies was conducted using the Newcastle–Ottawa Scale. Country-specific proportion of individuals with COVID-19 who developed ARDS and reported death were combined in a random-effect meta-analysis to give a pooled mortality estimate of ARDS. Results: The overall pooled mortality estimate among 10, 815 ARDS cases in COVID-19 patients was 39% (95% CI: 23–56%). The pooled mortality estimate for China was 69% (95% CI: 67–72%). In Europe, the highest mortality estimate among COVID-19 patients with ARDS was reported in Poland (73%; 95% CI: 58–86%) while Germany had the lowest mortality estimate (13%; 95% CI: 2–29%) among COVID-19 patients with ARDS. The median crude mortality rate of COVID-19 patients with reported corticosteroid use was 28.0% (lower quartile: 13.9%; upper quartile: 53.6%). Conclusions: The high mortality in COVID-19 associated ARDS necessitates a prompt and aggressive treatment strategy which includes corticosteroids. Most of the studies included no information on the dosing regimen of corticosteroid therapy, however, low-dose corticosteroid therapy or pulse corticosteroid therapy appears to have a beneficial role in the management of severely ill COVID-19 patients.